2020
DOI: 10.1038/s41598-020-63784-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lumbar spondylolysis and spondylolisthesis in patients with degenerative spinal disease

Abstract: Lumbar spondylolysis generally occurs in adolescent athletes. Bony union can be expected with conservative treatment, however, the fracture does not heal in some cases. When the fracture becomes a pseudoarthrosis, spondylolysis patients have the potential to develop isthmic spondylolisthesis. A cross-sectional study was performed to determine the incidence of spondylolysis and spondylolisthesis, and to elucidate when and how often spondylolisthesis occurs in patients with or without spondylolysis. patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 14 publications
3
33
0
2
Order By: Relevance
“…The prevalence of pseudoarthrotic spondylolysis in the Japanese general population had been reported to be 5.9%, and males (7.9%) showed a higher prevalence than females (3.9%) [9]. We also recently studied the prevalence of spondylolysis in the general population using CT data from patients undergoing CT scans of abdominal or lumbar regions for reasons other than low back disorders, and reported similar results to the previous report (total: 6.4%, male: 7.7%, female: 4.5%) [11].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The prevalence of pseudoarthrotic spondylolysis in the Japanese general population had been reported to be 5.9%, and males (7.9%) showed a higher prevalence than females (3.9%) [9]. We also recently studied the prevalence of spondylolysis in the general population using CT data from patients undergoing CT scans of abdominal or lumbar regions for reasons other than low back disorders, and reported similar results to the previous report (total: 6.4%, male: 7.7%, female: 4.5%) [11].…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, lumbar degenerative disease patients requiring spinal surgery showed similar prevalence of spondylolysis (6.5%) compared to the general population (5.9-6.4%) [9,11]. Therefore, these data suggest that the occurrence of severe degenerative lumbar disease requiring spinal surgery in patients with pseudoarthrotic spondylolysis is not higher than that in patients without spondylolysis.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Reconstructed CT images of the lumbar spine provide several benefits, such as more accurate measurement 3,5 and more detailed evaluation of bone morphology. 17,18 In conclusion, our data will be useful and provide normative values of lumbopelvic parameters in the supine position, for comparison in future clinical research. The present study first revealed age-related changes of lumbopelvic parameters in the supine position in males and females, suggesting a possibility that age-related decreases of LL and SS in females occur at an older age in the supine position than in the standing position.…”
Section: Discussionmentioning
confidence: 86%